Transferability and sustainability of motor-cognitive dual-task training in patients with dementia: a randomized controlled trial - Lemke, Nele; Werner, Christian; Wiloth, Stefanie; Oster, Peter; Bauer, Jürgen M.; Hauer, Klaus (Gerontology, 2019)
Background: Specific dual-task (DT) training is effective to improve DT performance in trained tasks in patients with dementia (PwD). However, it remains an open research question whether successfully trained DTs show a transfer effect to untrained DT performances. Objective:To examine transfer effects and the sustainability of a specific DT training in PwD. Methods:One hundred and five patients with mild-to-moderate dementia (Mini-Mental State Examination: 21.9 ± 2.8 points) participated in a 10-week randomized, controlled trial. The intervention group (IG) underwent a specific DT training (“walking and counting”). The control group (CG) performed unspecific low-intensity exercise. DT performance was measured under three conditions: (1) “walking and counting” (trained); (2) “walking and verbal fluency” (semi-trained), and (3) “strength and verbal fluency” (untrained). Outcomes evaluated at baseline, after training, and 3 months after the intervention period included absolute values for the motor and cognitive performance under DT conditions, and relative DT costs (DTCs) in motor, cognitive and combined motor-cognitive performance. Results:The IG significantly improved DT performances in the trained condition for absolute motor and cognitive performance and for motor, cognitive, and combined motor-cognitive DTCs compared to the CG (≤ 0.001-0.047; = 0.044-0.249). Significant transfer effects were found in the semi-trained condition for absolute motor and partly cognitive performance, and for motor but not for cognitive DTCs, and only partly for combined DTCs (≤ 0.001-0.041= 0.049-0.150). No significant transfer effects were found in the untrained condition. Three months after training cessation, DT performance in the trained condition was still elevated for most of the outcomes (p ≤ 0.001-0.038; ηp2 = 0.058-0.187). Training gains in the DT performance in the semi-trained condition were, however, not sustained, and no significant group differences were found in the DT performance in the untrained condition after the follow-up. Conclusion: This study confirmed that specific DT training is effective in improving specifically trained DT performances in PwD and demonstrated sustainability of training-induced effects for at least 3 months. Effects were partially transferable to semi-trained DTs but not to untrained DTs. With increasing distance between trained and untrained DTs, transferability of training effects decreased.